Adsorpsi Zat Warna Rhodamine B Dengan Karbon Aktif Kulit Durian sebagai Adsorben - Azhma Ulya; Edi Nasra; Ali Amran; Desy Kurniawati (Jurnal Periodic Jurusan Kimia UNP, 2022)
Rhodamine, B colorant is one of the dyes present in the waste coming from the textile/dyeing industry. Rhodamin B dyes found in waters can cause damage to ecosystems both animals and plants, so a method is needed to overcome the impact of pollution by Rhodamin B waste. One of the most efficient methods is the adsorption method using activated carbon from Durian peels. Adsorption,process is done by using a variation,of pH (2, 3, 4, 5 and 6), and variation of stirring speed (50, 100, 150, 200, 250 rpm). The results showed the absorption capacity at optimum conditions for the absorption of Rhodamine B at pH 4 and stirring speed at 200 rpm with absorption capacity of 24,643 mg/g with absorption percentage 96,0292%.